2023
DOI: 10.1257/app.20210190
|View full text |Cite
|
Sign up to set email alerts
|

A New Spatial Hedonic Equilibrium in the Emerging Work-from-Home Economy?

Abstract: This paper studies the impacts of work from home (WFH) in the housing market from both intercity and intracity perspectives. Our results confirm the theoretical prediction that WFH puts downward pressure on housing prices and rents in high-productivity counties, a result of workers starting to relocate to cheaper metro areas during the pandemic without forsaking their desirable jobs. We also show that WFH tends to flatten intracity house-price gradients, weakening the price premium associated with good job acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…These explanations and assumptions are consistent with the findings of Brueckner et al (2023) and Ramani and Bloom (2021) for cities in the USA, who found that the pandemic essentially led to a ‘donut’ effect in housing where the central ring of cities was deserted in favour of the suburbs. This is a phenomenon which may quite well be true for Indian cities too.…”
Section: Methodology and Data Sourcessupporting
confidence: 90%
See 1 more Smart Citation
“…These explanations and assumptions are consistent with the findings of Brueckner et al (2023) and Ramani and Bloom (2021) for cities in the USA, who found that the pandemic essentially led to a ‘donut’ effect in housing where the central ring of cities was deserted in favour of the suburbs. This is a phenomenon which may quite well be true for Indian cities too.…”
Section: Methodology and Data Sourcessupporting
confidence: 90%
“…The hybrid mode nonetheless means that the workforce cannot leave the cities now as they did earlier (moving to their hometowns or smaller cities in India). Due to this effect, some United States studies (Brueckner et al, 2023; Ramani & Bloom, 2021) found that the pandemic essentially led to a ‘donut’ effect in housing where the central ring of cities is deserted in favour of the suburbs. Melo (2022) found, unsurprisingly, that the pandemic setback public transport and sustainable urban mobility.…”
Section: Introductionmentioning
confidence: 99%
“…1-standard-deviation increase in the relative state marginal income tax rate associated with approximately 2.4% fewer moves, consistent with the theoretical predictions of Brueckner et al (2023) and the empirical results of Duchin and Sosyura (2021) on the location preferences of executives who work from home. These…”
supporting
confidence: 81%
“…Recent theoretical work predicts that the large-scale adoption of remote work will shift migration patterns both intracity and intercity (Brueckner et al (2023), Davis et al (2023), and ). Empirically, survey data from Ozimek (2020) estimate that 14-23-million Americans planned on moving in response to the increase in remote work capabilities, with more than half moving more than 2 hours away.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation